Legal diffusion as protectionism: the case of the U.S. promotion of antitrust laws - Arslan, Melike (Review of international political economy : RIPE, 2023)
Prior research on the global diffusion and harmonization of antitrust (competition) laws mainly focused on the motivations of countries newly adopting or reforming their national laws. This article instead inquires about the motivations of the powerful states promoting these laws internationally, primarily focusing on the United States. It finds that trade protectionist -rather than globalist- interests and ideas prompted the United States' promotion of strong international antitrust norms in the 1990s. Analyzing Congressional documents and debates in the 1980s, it shows that American import-competing companies framed foreign industrial policies as cartelization to legitimize their demands for trade protections within the dominant framework of free markets and domestic antitrust laws. The political salience of this narrative in Congress contributed to the preparation of the 1988 Trade Laws and the 1990 trade negotiations with Japan, which formalized the United States' preference for strong international antitrust norms during the 1990s. These findings highlight that, ironically, 'anti-market' reasons can also motivate 'pro-market' norm diffusion.